Two lives - Seth, Vikram 1952- (HarperCollins, 2005)
Shanti Behari Seth, brought up in India, was sent by his family in the 1930s to Berlin--though he could not speak a word of German--to study medicine and dentistry. Helga Gerda Caro, known to everyone as "Henny" was also born in 1908, in Berlin, to a Jewish family--cultured, patriotic, and intensely German. When the family decided to take Shanti as a lodger, Henny's first reaction was, "Don't take the black man!" But a friendship flowered, and when Henny fled Germany just one month before war broke out, she was met at Victoria Station by the only person in the country she knew: Shanti. Vikram Seth has woven together their story, which recounts the arrival into this childless couple's lives of their great-nephew from India--the teenage Vikram. The result is a tapestry of India, the Third Reich and the Second World War, Auschwitz and the Holocaust, Israel and Palestine, postwar Germany and 1970s Britain.--From publisher description.
Keywords: Seth, Vikram <1952-> - Enfance et jeunesse; Seth, Vikram <1952-> - Famille; Seth, Vikram <1952-> - Résidences et lieux familiers - Angleterre - Londres; Seth, Vikram -- 1952- -- Homes and haunts -- England -- London; Seth, Vikram -- 1952- -- Childhood and youth; Seth, Vikram -- 1952- -- Family; Seth, Vikram -- 1952-; Geschichte 1900-2000; Geschichte 1908-2004; Geschichte 1940-2000; Familieleden; Immigranten; Indiens (Habitants de l'Inde) - Angleterre - Londres; Mariage interracial - Angleterre - Londres; Rassenverhoudingen; Écrivains anglais - 20e siècle - Biographies; Écrivains de l'Inde - Résidences et lieux familiers - Angleterre - Londres; Alltag, Brauchtum; Authors, Indic -- Homes and haunts -- England -- London; Authors, English -- 20th century -- Biography; Interracial marriage -- England -- London; East Indians -- England -- London; Onkel; Inder; Ehe; Deutsche Frau; Erinnerung; Tante; Lebenslauf; Familie; Londres (Angleterre) - Biographies; Londres (Angleterre) - Murs et coutumes - 20e siècle; London (England) -- Social life and customs -- 20th century; London (England) -- Biography; Großbritannien; Autobiografie -- 1969-2004; Erlebnisbericht